Workshop on Interactive Teaching for Young Learners - Nadia, Hafizhatu; Rafidiyah, Dina Rafidiyah; Yansyah, Yansyah (Comment: an International Journal of Community Development, 2019)
Introducing young learners to learn a foreign language need extra efforts. It is due to the unique characteristics of young learners which require the teacher to live up the classroom’s atmosphere to engage them during the lesson. The present article elaborates the interactive instructional strategies can be used by teachers for teaching them. Thirty-eight students in the “Sentosa” orphanage and five caregivers joined the workshop to experience the practice of interactive teaching. The interactive teaching worked out three games, including I See Something, Spelling Bee, and Board Race. Questionnaire was given after the workshop and observation was also conducted so the students’ responses toward the strategies can be recorded. The result indicated that most of the young learners love to learn through those games. The interaction among them were also intense so it fostered the process of acquiring the new vocabulary. The teachers also commented that this strategy was fun and interesting.